Comparative analysis of the proposals from Rio de Janeiro and Bahia for the sporting regulation of capoeira (1968) - Ana Rosa Jaqueira; Paulo Coêlho de Araújo (Universidad de León, 2012)
Background and aim: Despite having been institutionalised in the Brazilian Confederation of Pugilism (1941) as a sport, at that time there were not any regulations for Capoeira competitions. Two symposia (1968 and 1969) were held in Rio de Janeiro (Guanabara) aiming to establish a set of regulations for the discipline and, as a consequence, to provide equal conditions for the competing athletes. In order to do so, representatives from Bahia and Rio de Janeiro were invited to discuss the matter. The present study analyses the first three proposals for the regulation of Capoeira, which came from the states of Bahia and Rio de Janeiro and were presented at the symposium held in 1968. Method: The ethnographic and historical methods were used along with content analysis, praxeological analysis and semi-structured interviews for the survey, processing and interpretation of data, and subsequent comparison of the proposals. Results: We observed that the proposal from Bahia was characterised by gymnastic, recreational and ritual elements, whereas those from Rio de Janeiro were characterised by the agonistic aspect of the discipline. Differences regarding personal and stylistic views and territorial interests proved to be a major hindrance and no regulations were established. Therefore, we conclude that the ideal conditions for the sporting regulation of Capoeira could not be met at that time.